2005
DOI: 10.1105/tpc.105.033183
|View full text |Cite
|
Sign up to set email alerts
|

Rab11 GTPase-Regulated Membrane Trafficking Is Crucial for Tip-Focused Pollen Tube Growth in Tobacco

Abstract: Pollen tube growth is a polarized growth process whereby the tip-growing tubes elongate within the female reproductive tissues to deliver sperm cells to the ovules for fertilization. Efficient and regulated membrane trafficking activity incorporates membrane and deposits cell wall molecules at the tube apex and is believed to underlie rapid and focused growth at the pollen tube tip. Rab GTPases, key regulators of membrane trafficking, are candidates for important roles in regulating pollen tube growth. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
188
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(206 citation statements)
references
References 98 publications
9
188
2
3
Order By: Relevance
“…Although the results presented herein are the first instance in which the temporal characteristics of exocytosis have been measured directly during oscillatory pollen tube growth, other studies have recorded the appearance of material at the cell surface (de Graaf et al, 2005;Lee et al, 2008) and attempted to infer the temporal properties. For example, Lee et al (2008) noted that RabA4d, which brightly stained the inverted cone in tobacco pollen tubes, appeared to oscillate with a component close to the apex anticipating growth.…”
Section: Exocytosis Has Been Studied In Other Pollen Tubesmentioning
confidence: 99%
“…Although the results presented herein are the first instance in which the temporal characteristics of exocytosis have been measured directly during oscillatory pollen tube growth, other studies have recorded the appearance of material at the cell surface (de Graaf et al, 2005;Lee et al, 2008) and attempted to infer the temporal properties. For example, Lee et al (2008) noted that RabA4d, which brightly stained the inverted cone in tobacco pollen tubes, appeared to oscillate with a component close to the apex anticipating growth.…”
Section: Exocytosis Has Been Studied In Other Pollen Tubesmentioning
confidence: 99%
“…Several reports have shown that small G-proteins and their effectors play important roles in polar growth (e.g., Molendijk et al, 2001;Jones et al, 2002;Preuss et al, 2004;de Graaf et al, 2005;Carol et al, 2005;Gu et al, 2005Gu et al, , 2006Song et al, 2006;Nielsen et al, 2008). Rab11 proteins from mammals are localized in the recycling endosome of polarized epithelial cells.…”
Section: Raba2 Is Important For Genesis and Growth Of The Root Hairmentioning
confidence: 99%
“…This apical localization of Rab11 and polarized actin organization are disrupted in dominantnegative and constitutively active mutants. Alteration of Rab11 activity also inhibited targeting of exocytic and recycled vesicles to the inverted cone region of the pollen tube and compromised the delivery of secretory and cell wall proteins to the extracellular matrix, suggesting that a proper regulation of Rab11 activity is essential for tip-focused membrane trafficking and growth at the pollen tube apex (de Graaf et al, 2005). Additional evidence of a connection between Rab proteins and polar growth comes from the characterization of a member of the Arabidopsis RABA4 subclass, RABA4b, which localizes to the trans-Golgi network compartment in the tip of growing root hairs (Preuss et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (8) recently observed the expression of nine different Rab isoforms (Rab4, Rab5, Rab8, Rab11, Rab13, Rab15, Rab27b, Rab28, and Rab32) in the uroepithelium and at least one of them, Rab27b, is associated with DFV; however, which Rabs regulate DFV exocytosis remains an open question. Although Rab27b is one possibility, an additional candidate includes Rab11 (a and b isoforms), which regulates trafficking pathways along both the endocytic and biosynthetic routes of polarized epithelial and neuroendocrine cells (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, the function of Rab11 in modulating the regulated secretory pathways of polarized epithelial cells has not been explored and nothing is known about the role of Rab11 in mechanotransduction or DFV exocytosis.…”
mentioning
confidence: 99%